Risk Aversion, Entrepreneurial Attitudes, Intention and Entry Among Young People in Uganda and Germany: A Gendered Analysis - Mabunda Baluku, Martin; Nansubuga, Florence; Otto, Kathleen; Horn, Lisa (Journal of Entrepreneurship and Innovation in Emerging Economies, 2021)
Extant research has consistently indicated that personality and cultural variables are important predictors of entrepreneurial behaviour and outcomes. Using a longitudinal approach, the article examines the effects of risk aversion on general entrepreneurial attitudes, entrepreneurial intentions and entry into self-employment, as well as how these effects differ according to gender and country contexts. Study 1 (T1) assessed risk aversion, entrepreneurial attitude and intentions among 573 students in the final year of their studies (284 at a German university and 289 at a Ugandan university). Study 2 (T2) established participants’ employment status 6–24 months after graduation. We were able to match 104 valid responses. Our results revealed negative effects of risk aversion on both general entrepreneurial attitude and intention. A moderated mediation effects model suggesting that risk aversion predicts entrepreneurial intention through general entrepreneurial attitude shaped by gender and country was confirmed. Moreover, risk aversion and entrepreneurial intentions had substantial effects on the likelihood of being self-employed while country differences were also observed.
Keywords: Country differences; Entrepreneurial attitude; Entrepreneurial intention; Gender differences; Risk aversion; Self-employment entry